Evaluasi Pengelolaan Limbah Padat Bahan Berbahaya dan Beracun (B3) Di PT. A Bandung - Mila Dirgawati; Dzakiyyah Afifah Aurora (Jurnal Serambi Engineering, 2024)
As part of its operations, PT A, a corporation specializing in military equipment, generated solid hazardous waste. Their four distinct forms of solid hazardous waste are contaminated hazardous waste, used rags, wastewater sludge, and blasting residue. This study aims to analyze and assess the utilized Guttman scale in order to determine the origins and kinds of hazardous solid waste, as well as its characteristics, quantity, and management system. Based on these findings, recommendations and proposals will be provided. With an 88% score, PT A was deemed "Very Good" according to the findings. It is suggested that workers be educated to raise knowledge about the need to separate household trash from hazardous waste. Additionally, a monitoring system should be put in place to check the process on a regular basis, and decisive action should be taken to create a safer atmosphere.